Technological advances in free-circulating tumor-derived DNA methylation analysis: Advances in ctDNA methylation analysis - Skalski, Marcin; Paluszczak, Jarosław (Journal of Medical Science, 2019)
Cancers still constitute an important health burden, due to their high incidence and mortality. The discovery and clinical implementation of novel sensitive diagnostic markers could improve treatment outcomes. Circulating cell-free DNA (ccfDNA) offers great promise for the development of new molecular biomarkers. However, the analysis of ccfDNA methylation poses significant challenges due to ccfDNA fragmentation and low concentration in the blood. Techniques which have recently been developed for liquid biopsy studies have been adapted to the detection of trace amounts of ccfDNA. This mini-review focuses on recent technological advances which allow the discovery of new sensitive and specific liquid biopsy cancer biomarkers based on DNA methylation detection.
Keywords: cancer; biomarkers; liquid biopsy; circulating cell-free DNA; cfDNA; DNA methylation